Dopaminergic neurons preferentially accumulate mtDNA rearrangements - Tania Arguello; Christian D. Alcalde Pretel; Nadee Nissanka; Derek Van Booven; Milena Pinto; Monica Rodriguez-Silva; Lise-Michelle Theard; Anthony J. Griswold; Carlos T. Moraes (Proceedings of the National Academy of Sciences, 2026)
High levels of mitochondrial DNA (mtDNA) deletions have been described in the substantia nigra. However, the mechanisms involved are poorly understood. We found that transient expression of a mitochondrial targeted restriction endonuclease (mitoPstI) in mice leads to an accumulation of mtDNA rearrangements that involve both the PstI cleavage sites and unrelated specific regions of the mtDNA, including the MTERF1 binding site and the edge of the D-loop. This pattern of rearrangements after double-strand breaks supports the presence of recombination hotspots in the mtDNA. Transient expression of mitoPstI in dopaminergic neurons led to further accumulation of mtDNA rearrangements in dopaminergic neurons after expression was suppressed, a pattern that was not observed in glutamatergic neurons. This accumulation was also blunted when a mtDNA replisome factor was absent, suggesting that robust mtDNA replication is required for the accumulation of preexisting mtDNA rearrangements in dopaminergic neurons over time.